Aspectos fitotécnicos e qualidade do solo em sistemas agroecológicos no feijoeiro comum (Phaseolus vulgaris L.) - Herrada, Marisol Rivero (2013)
The study was on the effect of agroecosystems in common bean (Phaseolus vulgaris L). The objective was to evaluate phytotechnical aspects and soil quality in agroecosystems using legumes in monoculture and intercropped with millet system and conventional tillage in the common bean. The legumes studied were beans pork (Canavalia ensiformes), Crotalaria (Crotalaria juncea), Mucuna (Stizolobium dierrigianum) , Guandu (Cajanus cajan) in monoculture and intercropped with millet (Penicetum glaucum) under conventional and no-tillage system. The experiment was conducted in a randomized block design. Dry biomass, nutrient content, nutrient accumulation of plants for roofs, growth (height and stem diameter) of plants, yield of common bean and the physical , chemical and biological soil properties were evaluated . It was found that all legumes in monoculture and intercropped with millet provide high accumulation of nutrients in the biomass, contributing to the improvement of soil fertility and crop productivity in the common bean agroecosystem , the production of dry biomass cover crops were exceeding 9.000 Mg ha-1 , stood out the pigeon pea and bean Mucuna with the largest production fitomasssa and levels of N, P , Ca , Mg and Zn. The cropping system -tillage and legume consortium with millet allow better growth of the common bean. The yield of common bean was high for all systems, the highlight was the bean pork with the highest yield. The soil physical properties were not affected by agroecological systems. Chemical and biological soil properties were altered with high accumulations of nutrients supplied to the ground in agroecosystems. The system was used as a cover crop showed the lowest metabolic coefficient, and the system more efficient.